Spatial summation improves bird color vision in low light intensities. (January 2017) - Olsson, Peter; Wilby, David; Kelber, Almut
Abstract: Color guides many important behaviors in birds. Previously we have shown that the intensity threshold for color discrimination in the chicken depends on the color contrast between stimuli and their brightness. The birds could discriminate larger color contrasts and brighter colors in lower light intensities. We suggested that chickens use spatial summation of cone signals to maintain color vision in low light levels. Here we tested this hypothesis by determining the intensity thresholds of color discrimination using similar stimuli, patterns of grey tiles of varying intensity interspersed with color tiles, adjusted for this specific aim. Chickens could discriminate stimuli with a larger single color tile, or with a larger proportion of small color tiles, in lower light intensities. This is in agreement with the hypothesis that spatial summation improves color discrimination in low light levels. There was no difference in the intensity threshold for discrimination of stimuli with a single 6 × 6 mm color tile, stimuli with 30% colored tiles and stimuli in which color filled the whole pattern. This gives a first indication to the degree of spatial summation that can be performed. We compare this level of spatial summation to predictions from mathematical model calculations.